2010
DOI: 10.1002/pbc.22561
|View full text |Cite
|
Sign up to set email alerts
|

Impact of continuous renal replacement therapy on oxygenation in children with acute lung injury after allogeneic hematopoietic stem cell transplantation

Abstract: Background Acute lung injury (ALI) continues to carry a high mortality rate in children after allogeneic hematopoietic stem cell transplant (HSCT). Continuous renal replacement therapy (CRRT) is often used for these patients for various indications including renal failure and fluid overload, and may have a beneficial effect on oxygenation and survival. Therefore, we sought to determine the effect of CRRT on oxygenation in mechanically ventilated pediatric allogeneic HSCT patients with ALI, and to document surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…In addition, the conditioning regimen may be associated with renal toxicity and with some degree of systemic inflammatory response syndrome accompanied by a capillary leak syndrome [74]. …”
Section: Reviewmentioning
confidence: 99%
“…In addition, the conditioning regimen may be associated with renal toxicity and with some degree of systemic inflammatory response syndrome accompanied by a capillary leak syndrome [74]. …”
Section: Reviewmentioning
confidence: 99%
“…Although it has not become a standard protocol for ARDS treatment, using CRRT to support ARDS treatment has been studied and reported in several medical centers for the past decade. 22 However, Hoste et al 36 found neither benefit nor harm about CRRT on oxygenation in patients with ARDS and acute kidney injury (AKI). These studies showed the therapeutic benefits of CRRT in ARDS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of fluid to administer in critically ill patients with ALI and ARDS has also been debated (118)(119)(120)(121). Adult studies have shown that hypoproteinemic patients may be twice as likely to develop ALI and three times more likely to die after its onset (122).…”
Section: Strong Agreementmentioning
confidence: 99%
“…Greater fluid overload at the initiation of CRRT, after adjusting for illness severity, has been associated with increased mortality in critically ill children (113)(114)(115)(116)(117)(118). In a retrospective analysis of CRRT use in pediatric allogeneic hematopoietic stem cell transplantation patients requiring mechanical ventilation for ALI, CRRT significantly improved oxygenation which correlated with reduction in fluid balance (118). Further studies are needed to determine the role of CRRT in fluid management of PARDS.…”
Section: Strong Agreementmentioning
confidence: 99%